Effect of in-situ greengram (Phaseolus radiatus) residue and nitrogen levels on toria (Brassica rapa) in rice (Oryza sativa) - greengram-toria sequence in Ultic Haplustalf - DEY, J K; PAUL, S R (The Indian Journal of Agricultural Sciences, 2013)
Residual effect of in-situ greengram (Phaseolus radiatus L.) straw incorporation and N levels on succeeding toria(Brassica rapa (L.) Thell. emend. Metzer; syn B. Campestris L. ssp oleifera (Metzger) Sinsk. var toria) in rice (Oryzasativa L. ) - greengram - toria sequence was studied in Ultic Haplustalf during 1995-97. Grain and straw yield as well asNPK uptake of toria were significantly higher in rice - green gram -toria sequence than fallow toria sequence. Under bothcropping systems, tori a responded upto 40 kg N/ha. Residual effect of greengram straw incorporation was equivalent to40 kg N/ha. As compared to initial soil status, riceÂ· greengram -toria sequence recorded higher organic matter, total N aswell as water holding capacity. The pH, available P and K recorded higher reduction in soils under fallowÂ· toria than rice-grecngram - toria sequence